2006 International Workshop on Virtual Rehabilitation 2006
DOI: 10.1109/iwvr.2006.1707550
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Within a Dynamic Virtual Environment

Abstract: Background: Planning and execution of reaching requires a series of computational processes that involve localization of both the target and initial arm position, and the translation of this spatial information into appropriate motor commands that bring the hand to the target. We have investigated the effects of shifting the visual field on visuomotor control using a virtual visual environment in order to determine how changes in visuo-spatial relations alter motor planning during a reach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…For example, Viau et al (2004) showed that arm movement trajectories of both healthy subjects and individuals with mild hemiparesis following stroke were smooth and followed similar paths during reaching, grasping and placing a ball in both virtual and real physical environments. In accordance with these earlier studies, we have previously reported that subjects were able to reach toward all single- and double-step targets as well as to amend their ongoing movement in response to the unpredictable target displacement, while performing in the VE (Dvorkin et al 2007). Whereas similar behavior during a double-step task has been shown in the past for reaching within a stable VE (Martin et al 2003), we have now demonstrated that this holds true for both the still and dynamic scene conditions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, Viau et al (2004) showed that arm movement trajectories of both healthy subjects and individuals with mild hemiparesis following stroke were smooth and followed similar paths during reaching, grasping and placing a ball in both virtual and real physical environments. In accordance with these earlier studies, we have previously reported that subjects were able to reach toward all single- and double-step targets as well as to amend their ongoing movement in response to the unpredictable target displacement, while performing in the VE (Dvorkin et al 2007). Whereas similar behavior during a double-step task has been shown in the past for reaching within a stable VE (Martin et al 2003), we have now demonstrated that this holds true for both the still and dynamic scene conditions.…”
Section: Discussionsupporting
confidence: 86%
“…In a previous study with a small number of subjects we have described preliminary observations on the effect of roll visual motion on reaching, where subjects were exposed to an immersive 3D VE which was either matched to their head motion or rolled counterclockwise for a short time at a constant velocity (Dvorkin et al 2007). We have found that motion of the visual field mainly affected reaching toward a remembered target location.…”
Section: Introductionmentioning
confidence: 99%
“…2.4.2 Remapped Input. Perception manipulation techniques have also been employed in selection-type tasks, where users' hands are retargeted to manipulate position and rotation to enable distantobject selection or to make selection more comfortable [18,20,[24][25][26]56]. These techniques are especially important when users are located in constrained spaces such as plane seats, where larger reaching motions may not be possible.…”
Section: Perception Manipulation Techniques Andmentioning
confidence: 99%
“…MacKenzie et al [23] investigated real time kinematics of limb movements in a Fitts' task and showed that, while Fitts' Law holds for the total limb-movement time, humans decelerate the motion sooner, if the target seems to require more precision in the end phase. The changes of the kinematics and control for reaching tasks within virtual environments have been investigated [14,38].…”
Section: D Mid-air Interaction Techniquesmentioning
confidence: 99%